Mechanical and Non‐Mechanical Functions of Filamentous and Non‐Filamentous Vimentin. (6th September 2020) - Patteson, Alison E.; Vahabikashi, Amir; Goldman, Robert D.; Janmey, Paul A.
Abstract: Intermediate filaments (IFs) formed by vimentin are less understood than their cytoskeletal partners, microtubules and F‐actin, but the unique physical properties of IFs, especially their resistance to large deformations, initially suggest a mechanical function. Indeed, vimentin IFs help regulate cell mechanics and contractility, and in crowded 3D environments they protect the nucleus during cell migration. Recently, a multitude of studies, often using genetic or proteomic screenings show that vimentin has many non‐mechanical functions within and outside of cells. These include signaling roles in wound healing, lipogenesis, sterol processing, and various functions related to extracellular and cell surface vimentin. Extracellular vimentin is implicated in marking circulating tumor cells, promoting neural repair, and mediating the invasion of host cells by viruses, including SARS‐CoV, or bacteria such as Listeria and Streptococcus . These findings underscore the fundamental role of vimentin in not only cell mechanics but also a range of physiological functions. Also see the video abstract here https://youtu.be/YPfoddqvz-g . Abstract : Vimentin forms a wickerwork network that provides mechanical protection of the nucleus and elasticity to the cytoskeleton. New work highlights vimentin's life outside the cell. It is secreted by multiple cell types and can provide positive signals for wound healing and act as a cofactor for pathogen infection.